Internet of Educational Things (IoET): An Overview - Zahid Zufar At Thaariq (Universitas Negeri Surabaya or The State University of Surabaya, 2024)
The internet has caused a paradigm shift in education towards digitalization, so that students who experience it are now referred to as digital natives. This technology has changed the orientation of learning and teaching from teacher-centered to student-centered. Specific discussion is needed regarding the use of the internet modified in such a way in learning. Internet of Educational Things (IoET) becomes an interesting discussion in this article to support the paradigm shift. This article discusses using a narrative review approach. This means that this preparation tends to be reflective and in accordance with the author's understanding. The discussion includes (1) the paradigm shift from conventional to internet-assisted digital, (2) IoET as a digital-based instructional system approach and (3) related findings. Future recommendations will be presented, especially regarding the use of IoET in the education system.